Implementing the Bologna Process in the Romanian Higher Economic Education System - Văcărescu Hobeanu, Loredana (Journal of Research in Educational Sciences; Vol 4 No 1 (2013): JRES, Volume IV, Issue 1(6), 2013, 2013)
In order to ensure the comparability in the standards and quality of the higher education qualifications of all European countries’ educational systems, the ministers of education of the European countries signed the Bologna Declaration in 1999. The establishment of a modern, competitive and specific European management vision is the new philosophy behind the education system promoted by the reform of the European higher education through the Bologna Process. Among its key guidelines we find quality assurance in education, excellence in research, a higher degree of performance, raising the level of competitiveness, student-centered learning, new strategies and approaches to teaching, fostering creativity and innovation, focus on the learning outcomes, the pragmatism of education, the close relationship between education and the labor market.